Representative Percentile Curves of Physical Fitness From Early Childhood to Early Adulthood: The MoMo Study - Niessner, Claudia; Utesch, Till; Oriwol, Doris; Hanssen-Doose, Anke; Schmidt, Steffen C. E.; Woll, Alexander; Bös, Klaus; Worth, Annette (Frontiers in Public Health, 2020)
Introduction: The aim of this analysis is to report sex- and age-specific physical fitness percentile curves from childhood to early adulthood in a nationwide sample in Germany. Already in childhood, physical fitness is considered as one of the most important health markers. From a developmental and preventive perspective, physical fitness levels are relatively stable from childhood to early adulthood. Thus, it is important to monitor physical fitness on a population based level being able to intervene at early stages. Methods: Data stem from the nationwide representative Motorik Modul (MoMo) Study in Germany (data collection wave 1: 2009–2012; age: 4-23 y.; n=3,742; 50.1% female). Physical fitness was assessed by means of the MoMo test profile covering four dimensions of physical fitness (strength, endurance, coordination, flexibility). Percentile curves were fitted using the LMS transformation method of Cole and Green. Results: Standardized age- and sex-specific physical fitness percentiles were calculated for eight items covering health-related (endurance, strength endurance, maximal strength, flexibility) and skill-related fitness dimensions (balance, coordination). Percentile-curve-shapes differ between sexes. Physical fitness improvements with age are linear (e.g. max. strength) or curvilinear (e.g. coordination) depending on physical fitness dimension. Discussion: Our results provide for the first time sex- and age-specific physical fitness percentile curves for Germany from childhood to early adulthood. Differences in curve-shapes indicating a timed and capacity-specific physical fitness development. Nationwide German physical fitness percentiles can be useful in comparing populations (e.g. cross-country) and assessing initiatives that aim to improve childhood physical fitness.